2020
DOI: 10.1515/tnsci-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

EGCG modulates PKD1 and ferroptosis to promote recovery in ST rats

Abstract: AbstractBackgroundSpinal cord injury (SCI) causes devastating loss of function and neuronal death without effective treatment. (−)-Epigallocatechin-3-gallate (EGCG) has antioxidant properties and plays an essential role in the nervous system. However, the underlying mechanism by which EGCG promotes neuronal survival and functional recovery in complete spinal cord transection (ST) remains unclear.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…We believe that EGCG is a candidate phytochemical. A large number of studies have demonstrated that EGCG could affect the expression of specific proteins and signal pathways, such as AMPK and related pathways [ 28 , 30 , [60] , [61] , [62] ], and intervene in a variety of RCD forms, such as autophagy, apoptosis, and ferroptosis [ [34] , [35] , [36] , [63] , [64] , [65] ], all of which confirm its pharmacological characteristics, multiple targets, and underlying mechanisms [ 24 , 25 ]. Our results revealed that in DIC, EGCG pretreatment effectively decreased iron accumulation, inhibited excess ROS generation and oxidative stress, and rectified abnormal lipid metabolism in vitro and in vivo, which was similar to the intervention effects of the ferroptosis inhibitor Fer-1 [ 19 , 20 ], iron chelator Dxz [ 52 , 58 ], and mitochondrial free radical scavenger MitoTEMPO [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that EGCG is a candidate phytochemical. A large number of studies have demonstrated that EGCG could affect the expression of specific proteins and signal pathways, such as AMPK and related pathways [ 28 , 30 , [60] , [61] , [62] ], and intervene in a variety of RCD forms, such as autophagy, apoptosis, and ferroptosis [ [34] , [35] , [36] , [63] , [64] , [65] ], all of which confirm its pharmacological characteristics, multiple targets, and underlying mechanisms [ 24 , 25 ]. Our results revealed that in DIC, EGCG pretreatment effectively decreased iron accumulation, inhibited excess ROS generation and oxidative stress, and rectified abnormal lipid metabolism in vitro and in vivo, which was similar to the intervention effects of the ferroptosis inhibitor Fer-1 [ 19 , 20 ], iron chelator Dxz [ 52 , 58 ], and mitochondrial free radical scavenger MitoTEMPO [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports revealed that EGCG protected mouse intestinal epithelial cells and alleviated ionizing radiation-induced ferroptosis [ 34 ], iron overload and erastin-induced pancreatic cell ferroptosis [ 35 ]. Furthermore, it was found to promote PKD1 phosphorylation and inhibit ferroptosis after spinal cord injury [ 36 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Kose et al discovered that EGCG protected pancreatic cells against erastin-induced ferroptosis through chelating iron and preventing GSH depletion and lipid peroxidation [ 101 ]. Inhibition of ferroptosis by EGCG reduced oxidative stress and promoted recovery in spinal cord transection rats [ 108 ]. In addition, Nrf2 and its downstream targets comprising antioxidant proteins SLC7A11, HO-1 and GPX4 are essential for the radioprotective effects of EGCG in HIEC cells [ 109 ].…”
Section: Natural Bioactive Compounds As Ferroptosis Regulatorsmentioning
confidence: 99%
“…In our previous study, we revealed that EGCG can exert neuroprotective roles in BPRA and SCI [ 8 , 38 ]. In the present study, we revealed that EGCG upregulated miR-137-3p, inhibited neuronal Parthanatos, and reduced oxidative stress to promote the functional recovery and alleviate ICH-induced brain injury in mice following ICH.…”
Section: Discussionmentioning
confidence: 99%
“…The ELISA was performed, as previously described [ 37 , 38 ]. The segment of perihematoma in the ipsilateral cortex was obtained.…”
Section: Methodsmentioning
confidence: 99%